Gerenciamento de resultados e decisões de investimentos no Brasil - Souza, Arthur da Silva (2018)
The objective of this dissertation is to examine the relationship between earnings management through accruals and real activities with overinvestment of companies. The earnings management practices are analyzed through the regression residuals (erros) for each results management model, which represent the abnormal level of the activities and is a proxy for management identification. The level of investments considered ideal is that which occurs due to the investment opportunities of the company and the deviation in the level of investment is the overinvestment or underinvestiment to the level that would be ideal. To identify investment levels, a model based on economic literature will be used as proposed by McNichols and Stubben (2008). To achieve this objective the investments in assets will be analyzed for a sample of 1,240 non-financial companies listed on the BMF&FBOVESPA during the period from 2011 to 2017, collected from the Thomson Reuters Eikon system. For the operationalization of the research, it was chosen to use the method of Fama and Macbeth (1973) for panel data. The results showed that overinvestment is positively and significantly associated to the earnings management through accruals and discretionary revenues, indicating that companies use both management practices to report a better result. In contrast, in reference of management by real activities, was found evidences that companies use less this modality that, when used, is not necessarily to report better results in the period. Finally, the evidence suggests that management practices, generally used to achieve objectives external to the company, may also be associated with investment decisions.